A reinforcement learning agent for head and neck intensity-modulated radiation therapy - Stephens, Hunter; Li, Xinyi; Sheng, Yang; Wu, Qiuwen; Ge, Yaorong; Wu, Q. Jackie (Frontiers in Physics, 2024)
Head and Neck cancers pose a difficult problem in the planning of Intensity Modulated Radiation Therapy (IMRT) treatment. The primary tumor can be large and asymmetrical and multiple organs at risk with varying dose sparing goals lie close to the target volume. Currently there is no systematic way of automating the generation of IMRT plans, and the manual options face plan quality and long planning time challenges. In this article, we present a reinforcement learning (RL) model for the purposes of providing automated treatment planning to reduce clinical workflow time as well as providing a better starting point for human planners to modify and build upon. Several models with progressing complexity are presented, including the relevant plan dosimetry analysis and model interpretations of the resulting strategies learned by the auto-planning agent. Models were trained on a set of 40 patients and validated on a set of 20 patients. The presented models are shown to be consistent with the requirements of an RL model to be underpinned by a Markov Decision Process (MDP). In-depth interpretability of the models is presented by examination of the decision space using action hyper-planes. The auto-planning agent was able to generate plans with superior reduction in the mean dose of the Left and Right Parotid glands by around 7 Gy ± 2.5 Gy (p < 0.01) over a starting, static template plan with only pre-defined general prescription information. RL plans were comparable to human expert's clinical plans for the primary (44 Gy), boost (26 Gy) plans, and the summed plans (70 Gy) with p-values of 0.43, 0.72, and 0.67 respectively, for the dosimetric endpoints and uniform target coverage normalization. The RL planning agent was able to produce the plans used in validation in an average of 13.58 minutes with a minimum and a maximum planning time of 2.27 and 44.82 minutes respectively.